Adipose derived stem cell conditioned medium effect on proliferation phase of wound healing in Sprague Dawley rat (Faculty of Medicine Universitas Indonesia, 2017)
Background: Disintegration of skin tissue can lead to disability and death. Recent studies on wound therapy applied stem cells and adipose derived stem cell conditioned medium (ADSC-CM) to improve wound healing. However, the role of ADSC-CM in wound healing mechanism in terms of angiogenesis, quantity of collagen, and epithelialization is not fully understood. Therefore, this study aimed to analyze the levels of growth factors (VEGF and EGF) in ADSC-CM and histological features of angiogenesis, epithelialization, and collagen density after skin incision in Sprague Dawley rats.Methods: Thirty rats were injured at the back (full thickness wound) and treated topically with ADSC-CM, culture medium, basal medium, and without treatment. Mice were sacrificed on days 3, 7, 14, 21 and 28. After sacrificed, tissue samples were examined microscopically to assess angiogenesis, epithelialization, and collagen density. Concentrations of VEGF and EGF in ADSC-CM were measured by ELISA.Results: Clinically, wound that was treated with ADSC-CM showed improvement in wound healing process. ADSC-CM treated wound showed the highest epithelialization ratio and the fastest wound closure.Conclusion: There were no statistical significant differences between groups that were treated with ADSC-CM and not. However, topical ADSC-CM treated wound revealed a better clinical improvement in epithelialization.